Search for ultra-high-energy photons from gravitational wave sources with the Pierre Auger - García, Beatríz (My University, 2023)
A search for time-directional coincidences of ultra-high-energy (UHE) photons above 10 EeV with gravitational wave (GW) events from the LIGO/Virgo runs O1 to O3 is conducted with the Pierre Auger Observatory. Due to the distinctive properties of photon interactions and to the background expected from hadronic showers, a subset of the most interesting GW events is selected based on their localization quality and distance. Time periods of 1000 s around and 1 day after the GW events are analyzed. No coincidences are observed. Upper limits on the UHE photon fluence from a GW event are derived that are typically at ∼7 MeV cm−2 (time period 1000 s) and ∼35 MeV cm−2 (time period 1 day). Due to the proximity of the binary neutron star merger GW170817, the energy of the source transferred into UHE photons above 40 EeV is constrained to be less than 20% of its total GW energy. These are the first limits on UHE photons from GW sources.
Keywords: Ultra high energy cosmic rays, Pierre Auger Observatory, Cosmic Rays